A Model for the Analysis of Ultimate Capacity of RC and PC Corroded Beams. (26th July 2018) - Recupero, Antonino; Spinella, Nino; Tondolo, Francesco
Abstract : Corrosion of steel in reinforced and prestressed concrete beams is very common for structures and infrastructures. It can drastically reduce the resisting section of rebar, modify the mechanical response of the steel rebar, and also determine cracking of the surrounding concrete because of the volume expansion effect of rust. Moreover, it heavily influences the bond between steel rebar and concrete. Few experimental tests are available in the literature, where the structural behavior of reinforced and prestressed concrete beams, in presence of corrosion of longitudinal and transversal reinforcement, is analyzed. A reduction of the bearing performance is observed with an increasing level of rebar corrosion. Indeed, a changing collapse mechanism is evidenced through the tests and may be addressed to the not obvious consequences of corrosion. In this paper, a physical model based on a consistent equilibrium and ultimate strength theory is employed in order to explain the residual capacity of corroded beams. The model is based on limit analysis, and it is able to take into account the interaction between shear, bending moment, and axial forces.